Mapping the digital gap: Djarindjin and Lombadina, West Kimberley, WA, community outcomes report 2022 ... - Featherstone, Daniel; Thomas, Julian; Ormond-Parker, Lyndon; Holcombe-James, Indigo; Hawkins, Leah; Kennedy, Jenny (RMIT University, 2024)
Mapping the Digital Gap is a 4-year research project working in partnership with local organisations in 10-12 remote First Nations communities, to generate a detailed account of digital inclusion and uses of digital services including news and media, track changes over time, and inform appropriate local strategies and services enabling informed decision making by remote Aboriginal and Torres Strait Islander people. It is being undertaken through RMIT University as part of Centre of Excellence for Automated Decision Making and Society, in partnership with Telstra. ...